A Tool for Designing and Studying Student-Centered Undergraduate Field Experiences: The UFERN Model. (8th December 2021) - O'Connell, Kari; Hoke, Kelly L; Giamellaro, Michael; Berkowitz, Alan R; Branchaw, Janet
Abstract: Undergraduate field experiences (UFEs), where students learn and sometimes live together in nature, are critical for the field-based science disciplines. The Undergraduate Field Experiences Research Network (UFERN) brings together UFE educators and researchers to improve and broaden participation in field education. Integrating research on UFEs and general STEM education and the expertise of the UFERN community, we present a model and evidence that describes the impact of intended student outcomes, student context factors, and program design factors on UFE student outcomes. The UFERN model is relevant for a diversity of UFE formats and the diverse students potentially engaged in them, and it supports the field science community to consider a range of ways students can engage with the field. The UFERN model can be applied to guide the design, implementation, and evaluation of student-centered UFEs and to guide research on the mechanisms underlying outcomes across UFE formats and disciplines.